Physical Activity Is Associated With Lower Long-Term Incidence of Anxiety in a Population-Based, Large-Scale Study - Svensson, Martina; Brundin, Lena; Erhardt, Sophie; Hållmarker, Ulf; James, Stefan; Deierborg, Tomas (Frontiers in Psychiatry, 2021)
Physical activity may prevent anxiety, but the importance of exercise intensity, sex-specific mechanisms, and duration of the effects remains largely unknown. We used an observational study design to follow 395,369 individuals for up to 21 years to investigate if participation in an ultralong-distance cross-country ski race (Vasaloppet) was associated with a lower risk of developing anxiety. Skiers in the race and matched non-skiers from the general population were studied after participation in the race using the Swedish population and patient registries. Skiers (n = 197,685, median age 36 years, 38% women) had a significantly lower risk of developing anxiety during the follow-up compared to non-skiers (adjusted hazard ratio, HR 0.48). However, among women, higher physical performance (measured as the finishing time to complete the race, a proxy for higher exercise dose) was associated with an increased risk of anxiety compared to slower skiing women (HR 2.00). For men, the finishing time of the race did not significantly impact the risk of anxiety. Our results support the recommendations of engaging in physical activity to decrease the risk of anxiety in both men and women. The impact of physical performance level on the risk of anxiety requires further investigations among women.